Web-Based Learning Media Improves Concept Understanding and Student Engagement: Media Pembelajaran Berbasis Web Mendorong Pemahaman Konsep dan Keterlibatan Siswa - Nurfatah, Fauzi; Suherman, Uman; Setiawan, Deddy (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Education quality in rural areas often faces challenges due to limited access to technology and conventional teaching methods that reduce student motivation. Specific Background: In SDN 3 Bojong, Bungbulang, traditional teaching dominated by lectures and textbooks resulted in suboptimal learning outcomes and low student engagement, especially in science subjects. Knowledge Gap: Limited studies have examined the use of web-based media in elementary schools in rural areas with restricted infrastructure. Aim: This study investigates how web-based learning media supports concept mastery and engagement in science lessons. Results: Using a quasi-experimental design with pre-test and post-test, significant differences were found between experimental and control groups. Post-test mean scores improved to 88.5, and 96% of students reached the mastery criterion. N-gain analysis showed a medium category improvement (0.6210 or 62.10%). Student interest was categorized as very high (94.44%). Novelty: This study highlights the successful implementation of web-based media in a rural elementary school context, showing its capacity to create interactive and enjoyable learning experiences. Implications: Findings support integrating web-based media as an accessible solution to foster conceptual understanding and engagement in resource-limited educational settings. Highlight Significant improvement in student concept understanding measured by pre-test and post-test High student engagement and interest after using web-based media Medium category learning gain (N-gain = 0.62) indicates effective learning process Keyword: Web-Based Learning Media, Concept Understanding, Student Engagement, Interactive Learning, Elementary Education